CRUSTAL STRUCTURE OF MAINLAND CHINA FROM DEEP SEISMIC SOUNDING DATA - Li S.; Fan J.; Mooney W.D. (My University, 2006)
Since 1958, about ninety seismic refraction/wide angle reflection profiles, with a cumulative length of more than sixty thousand kilometers, have been completed in mainland China. We summarize the results in the form of (1) a new contour map of crustal thickness, (2) fourteen representative crustal seismic velocity-depth columns for various tectonic units, and, (3) a Pn velocity map. We found a north-south-trending belt with a strong lateral gradient in crustal thickness in central China. This belt divides China into an eastern region, with a crustal thickness of 30-45 km, and a western region, with a thickness of 45-75 km. The crust in these two regions has experienced different evolutionary processes, and currently lies within distinct tectonic stress fields. Our compilation finds that there is a high-velocity (7.1-7.4 km/s) layer in the lower crust of the stable Tarim basin and Ordos plateau. However, in young orogenic belts, including parts of eastern China, the Tianshan and the Tibetan plateau, this layer is often absent. One exception is southern Tibet, where the presence of a high-velocity layer is related to the northward injection of the cold Indian plate. This high-velocity layer is absent in northern Tibet. In orogenic belts, there usually is a low-velocity layer (LVL) in the crust, but in stable regions this layer seldom exists. The Pn velocities in eastern China generally range from 7.9 to 8.1 km/s and tend to be isotropic. Pn velocities in western China are more variable, ranging from 7.7 to 8.2 km/s, and may display azimuthal anisotropy. © 2006.
Keywords: CHINA; CRUSTAL STRUCTURE; DEEP SEISMIC SOUNDING